3, 3'-Diindolylmethane inhibits patient-derived xenograft colon tumor growth by targeting COX1/2 and ERK1/2. (28th April 2019) - Tian, Xueli; Liu, KangDong; Zu, Xueyin; Ma, Fayang; Li, Zhi; Lee, MeeHyun; Chen, Hanyong; Li, Yan; Zhao, Yuzhou; Liu, Fangfang; Oi, Naomi; Bode, Ann M.; et al.
Abstract: 3, 3'-Diindolymethane (DIM) is a dimeric condensation product of indole-3-carbinol (I3C) that is found in broccoli and cabbage. Although DIM has been reported to exhibit anticancer properties against multiple tumor types, the direct target proteins of DIM have not been fully investigated. In the present study, we report that DIM is a novel COX1/2 and ERK1/2 inhibitor that suppresses growth of colon cancer in vitro and in vivo . To identify possible molecular targets of DIM, 11 potential candidate proteins were validated by an in vitro kinase or enzyme assay. We found that DIM directly inhibits COX1/2 and ERK1/2 protein activities in vitro . Additionally, the PGE2 production (COX-mediated metabolite) and phosphorylated RSK expression (ERK1/2 direct downstream kinase) were strongly suppressed by DIM in colon cancer cells. The inhibition of cell growth by DIM is dependent on the expression of COX1/2 or ERK1/2 proteins. Notably, oral administration of DIM suppressed patient-derived xenograft colon tumor growth in an in vivo mouse model. Overall these results suggest that DIM is a potent and dual COX1/2 and ERK1/2 inhibitor that might be used for chemotherapy against colon cancer. Highlights: DIM directly inhibits the activity of COX1/2 and ERK1/2. DIM directly binds to COX1/2 and ERK1/2. DIM suppresses colon cancer cell growth and induces apoptosis. Anticancer activity of DIM is dependent on the expression of COX1/2 or ERK1/2 proteins. DIM attenuates the growth of patient-derived xenograft colon tumors.